2010
DOI: 10.1002/elan.200900251
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth/Polyaniline/Glassy Carbon Electrodes Prepared with Different Protocols for Stripping Voltammetric Determination of Trace Cd and Pb in Solutions Having Surfactants

Abstract: To improve reproducibility, stability and sensitivity, a bismuth (Bi) thin film was coated on glassy carbon (GC) substrates which surfaces were modified with a porous thin layer of polyaniline (PANI) via multipulse potentiostatic electropolymerization to form Bi/PANI/GC electrodes (Bi/PANI/GCEs). The Bi/PANI/GCEs were used successfully for simultaneous detection and determination of Cd 2þ and Pb 2þ ions, and various parameters were studied with reference to square wave anodic stripping voltammetric (SWASV) sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…The semilogarithmic nature of the calibration curve at the higher concentration range can be ascribed to saturation of the polymeric film with silver species. A similar behavior has been described earlier [58,59]. Plot (d) in Fig.…”
Section: Analytical Performances Of the Developed Electrodes In The Dsupporting
confidence: 72%
See 1 more Smart Citation
“…The semilogarithmic nature of the calibration curve at the higher concentration range can be ascribed to saturation of the polymeric film with silver species. A similar behavior has been described earlier [58,59]. Plot (d) in Fig.…”
Section: Analytical Performances Of the Developed Electrodes In The Dsupporting
confidence: 72%
“…The results revealed that peak currents enhanced with time till 125 s and then remained constant, which may be due to the electrode saturation effects [58]. A preconcentration time of 100 s was used to prevent the saturation of the electrodes for higher silver ion concentration.…”
Section: The Effects Of Preconcentration Conditionsmentioning
confidence: 99%
“…Recently, modified electrodes based on incorporation of conducting polymer (CP) films have received considerable attention for the detection of trace heavy metals due to their superior electrical conductivities, good film formation capability and structural characteristics [20]. CP films deposited on electrode could enhance stripping responses toward detection of heavy metal [10].…”
Section: Introductionmentioning
confidence: 99%
“…These methods are highly reliable and sensitive, but they incur high cost and long processing time. Thus, anodic stripping voltammetry (ASV) becomes an alternative due to its high sensitivity, portability, realtime analysis and low cost [7].…”
Section: Introductionmentioning
confidence: 99%